Understanding Chefchaouen Traditional knowledge for a sustainable habitat - Dipasquale, Letizia (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2020)
The medina of Chefchaouen represents an architectural heritage of great value and its building culture constitutes a repertoire of knowledge to be safeguarded as an expression of cultural diversity in the relationship between society and nature. The volume presents the results of an in-depth research on the knowledge system that constitutes the local building culture of the medina, highlighting the characteristics of the construction systems, the risks to which the traditional heritage is subject, and its contribution to the development of a sustainable habitat. The book addresses the theme of the built heritage of the medina with an interdisciplinary approach, which includes architecture as part of a system that has to be studied along with the natural, social and cultural contexts.